Estratégias de enunciação em cartazes institucionais: campanhas do ministério da saúde - Barboza, Luiz Cláudio Gomes (2011)
This dissertation analyzes institutional advertising posters from campaigns against AIDS of the Brazilian Federal Government, divulged between 2008 and 2010, under the perspective of the French Semiotics Theory. Initially, it was presented the Semantics of Discourse Theory, which considers the text as a unit of meaning consisted by a plane of contents and a plane of expression. Then, considering the plane of contents, it was analyzed the general path of meaning, organized into three levels, the one of deep structure, the narrative and the discursive. The strategies were comprehended as choices made by the enunciator in order to persuade the enunciatee to use condoms. It was observed not only the procedures of the discourse syntax, which usually compound the argumentative resources, but also the discursive semantic and the plane of expression as a means used in the argument. Through the research, it was inferred that the success of these governmental campaigns, internationally recognized, seems to have been due, mainly, because of the simplicity of direct, daily and repetitive form of communication, in order to guide the Brazilian people to change their habits in relation of the practice of sexuality tying protection and pleasure.